Surface group-modified MXene nano-flake doping of monolayer tungsten disulfides - Tao, Ye (2021)
Exciton/trion-involved optoelectronic properties have attracted exponential amount of attention for various applications ranging from optoelectronics, valleytronics to electronics. Herein, we report a new chemical (MXene) doping strategy to modulate the negative trion and neutral exciton for achieving high photoluminescence yield of atomically thin transition metal dichalcogenides, enabled by the regulation of carrier densities to promote electron-bound trion-to-exciton transition via charge transfer from TMDCs to MXene. As a proof of concept, the MXene nano-flake-doped tungsten disulfide is demonstrated to obtain an enhanced PL efficiency of up to ∼five folds, which obviously exceeds the reported efficiency upon electrical and/or plasma doping strategies. The PL enhancement degree can also be modulated by tuning the corresponding surface functional groups of MXene nano-flakes, reflecting that the electron-withdrawing functional groups play a vital role in this charge transfer process. These findings offer promising clues to control the optoelectronic properties of TMDCs and expand the scope of the application of MXene nano-flakes, suggesting a possibility to construct a new heterostructure junction based on MXenes and TMDCs.